Epilepsy With Auditory Features: From Etiology to Treatment - Furia, Alessandro; Licchetta, Laura; Muccioli, Lorenzo; Ferri, Lorenzo; Mostacci, Barbara; Mazzoni, Stefania; Menghi, Veronica; Minardi, Raffaella; Tinuper, Paolo; Bisulli, Francesca (Frontiers in Neurology, 2022)
Epilepsy with auditory features (EAF) is a focal epilepsy belonging to the focal epileptic syndromes with onset at variable age according to the new ILAE Classification. It is characterized by seizures with auditory aura or receptive aphasia suggesting a lateral temporal lobe involvement of the epileptic discharge. Etiological factors underlying EAF are largely unknown. In the familial cases with an autosomal dominant pattern of inheritance several genes have been involved, among which the first discovered, LGI1, was thought to be predominant. However, increasing evidence now points to a multifactorial etiology, as familial and sporadic EAF share a virtually identical clinical characterization and only a few have a documented genetic background/etiology. EAF is a benign syndrome, often without apparent abnormalities detected by neurological examination. However, it must be underscored that total remission might be lower than expected and that treatment withdrawal might lead to relapses. Thus, a proper understanding of this condition is in order for better patient treatment and counseling. Further studies are still required to further characterize the many facets of EAF.